The identity clause in CJEU jurisprudence during the Covid period - Liakopoulos, Dimitris (Revista Internacional de Direito Público | RIDP, 2021)
The present research aims to verify the nature and extent of the identity clause and to establish the role that art. 4, par. 2 TEU is called to perform in the management of the aforementioned conflicts. More specifically, it is of interest to verify whether the law has its own autonomy, what consequences may result its being violated in the light of CJEU jurisprudence and what added value could have a consistent use of the identity clause in the context of the management of inter-arder conflicts affecting the national identity of member states. My paper is dedicated to the reformulation of the norm to its new systematic collocation and to the punitive character of the duty sanctioned by it. The precise and systematic study of the positions expressed as appropriate, by the European Commission (EC), the national governments, the referring courts and the Advocate General, is particularly useful for assessing (if and) how the CJEU has understood and applied article. 4, par. 2 TEU. ln this regard, it is important to underline that the human dimension of CJEU (i.e. the composition of the judging panei) is mostly neglected in the study of the identity clause as if there were a sort of congenital presumption of consistency and deliberative quality towards the institution. The study conducted here tries to show that the composition of the competent section is also irnportant and to respond in the next questions: What is the duty to observe the national identity with respect to the principies that regulate the relations between the legal system of the Union and member states laws? And with respect to the well-known national contrai system, as affirmed by numerous supreme and constitutional courts of the member states? What are the conditions for the application of art. 4, par. 2 TEU? How to distinguish the hypotheses covered by the identity clause from those related to other provisions of the treaties to protect state prerogatives? Can the infringement of the identity clause lead to the disregard of EU law in a single member state? lt is possible to usefully invoke art. 4, par. 2 TEUs to justify the application of an internai rule incompatible with Union law? lt is desirable to elaborate judicial standards that allow to determine if and to what extent the intervention of the union can be considered legitimate and necessary under the identity clause? And is it still necessary to anticipate inter-organizational conflict and to set up ex-ante contrai mechanisms to ensure respect for the national identity of member states?